MULCHING EFFECTS ON YIELD AND QUALITY OF LAVANDIN (Lavandula intermedia) - Tatarević, Sara; Gavrić, Teofil (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Lavandin (Lavandula intermedia) is a perenal aromatic plant from Lamiaceae family. Aromatic plants' qualitative and quantitative properties, including lavandin, depend on variety, environmental factors, and cultivation practices. This paper aimed to examine the impact of different mulch types on yield and bioactive compounds of lavandin. The treatments included different types of mulches (straw, alfalfa, agritela and control/without mulch). The field experiment had a split-plot design. Each plot contained ten replications. The tested traits were yield of inflorescences, contents of essential oil, contents of total phenols and total flavonoids, and antioxidant activity. The lowest amount of essential oil was recorded in the ˝agritela˝ treatment (5.0 mL/100g), and the highest in the ˝straw˝ treatment (6.4 mL/100g). The treatments with ̋straw˝ had the highest level of flavonoids contents (17.13 mg g-1 CAE), followed by the treatments with ̋alfalfa ̋ (14.03 mg g-1 CAE), ˝agritela˝ (12.25 mg g-1 CAE), and ̋control ̋ (10.32 mg g-1 CAE).